(untitled) (Texas Journal of Engineering and Technology, 2022)
The article considers the development of algorithms and software for solving the problem of image quality assessment by fuzzy logic methods, the selection of object contours in the image and its segmentation using the fuzzy sets apparatus The selection of the contours of an object in the image and its segmentation using the fuzzy sets apparatus.